Direct Determination of miR‐21 in Total RNA Extracted from Breast Cancer Samples Using Magnetosensing Platforms and the p19 Viral Protein as Detector Bioreceptor. Issue 10 (10th September 2014) - Torrente‐Rodríguez, R. M.; Campuzano, S.; López‐Hernández, E.; Granados, R.; Sánchez‐Puelles, J. M.; Pingarrón, J. M.
Abstract A novel magnetobiosensing approach for the rapid, sensitive and selective miR‐21 detection is reported involving the use of a specific RNA probe (antimiR‐21), streptavidin‐magnetic beads (Strep‐MBs), the siRNA Binding Protein p19 as detector bioreceptor, and amperometric detection with the H2O2/hydroquinone (HQ) system at disposable screen‐printed carbon electrodes. The magnetosensor exhibited a dynamic range from 1.4 to 10 nM and a detection limit of 4.2 fmol of synthetic target miR‐21 without any amplification step in 75 min. The usefulness of the approach was evaluated by analyzing total RNA (RNAt) extracted from metastatic breast cancer cell lines, human tissues and breast cytologies.